Evaluation of the Effect of Benzydamine Hydrochloride on the Intensity of Gag Reflex: A Randomized Single-Blind Clinical Trial - Mohammad Mehdi Torabi; Reyhaneh Shoorgashti; Farnaz Haji Fattahi; Simin Lesan (Shiraz University of Medical Sciences, 2024)
Statement of the Problem: Gag reflex is among the most common problems during dental and endoscopic procedures. Benzydamine hydrochloride is a non-steroidal anti-inflammatory medica-tion and a local anesthetic that might be useful in reducing the gag reflex. Purpose: This study aimed to evaluate the effects of benzydamine hydrochloride mouthwash on the intensity of the gag reflex.Materials and Method: In this randomized clinical trial study, 30 participants aged 21-26 with a gag trigger point index (GTPI) higher than 2 were divided into 2 groups. In the case group, 15 ml of 0.15% benzydamine hydrochloride mouthwash was gargled for 1 minute, and after 10 minutes GTPI test was conducted. In the control group, 4 puffs of 10% lidocaine spray were applied to the mucosa of the targeted area, and after 5 minutes, GTPI was measured. Participants were asked about the taste and smell of the medications. Results: GTPI was significantly reduced in both groups. In the lidocaine group, the GTPI score changed from 4.47 to 2.00 (P<0.001), and that for the benzydamine group was 4.20 to 1.47 (P<0.001). The variance rate of the gag reflex was -2.73 and -2.47 in the benzydamine group and lidocaine group, respectively. However, this reduction was not statistically significant between the two groups. Also, benzydamine mouthwash has a significantly better taste and smell than lido-caine (P= 0.001).Conclusion: The results of this study showed that benzydamine mouthwash could be used quite effectively in reducing the gag reflex.